Kontribusi Kontrol Diri terhadap Penggunaan Gadget Saat Belajar Siswa Kelas XI SMKN 3 Padang - Azura Mita; Linda Fitria; Rini Sefriani (Yayasan Literasi Sains Indonesia, 2024)
This study was conducted to determine the contribution of self-control the use of gadgets while studying for class XI students of SMK Negeri 3 Padang in the 2024/2025 academic year. The type of research used in this study is quantitative. The population of this study was 464 people, with a sample of 219 people taken using proportionate stratified random sampling. This study examines the contribution of self-control to the use of gadgets. The instrument used for data collection in this study was Likert scale questionnaire. Data analysis was carried out using statistical programs on SPSS 29 and Microsoft Excel computers. Based on the data analysis, the results of the hypothesis of the calculated rvalue were 0.586 while the rtable was 0.132 because the calculated r was greater than the rtable (0.586> 0.132) then H0 was rejected and H1 was accepted where there was a significant correlation between self-control and the use of gadgets while studying for class XI students of SMK Negeri 3 Padang. The contribution value between self-control and the use of gadgets was obtained 34%. Thus, the use of gadgets by students can be reduced, if students have good self-control, and the rest is influenced by other variables.